ANALISIS PENGARUH PROFITABILITAS, STRUKTUR MODAL, KEPEMILIKAN MANAJERIAL DAN DEWAN KOMISARIS INDEPENDEN TERHADAP NILAI PERUSAHAAN - Suri, Alfiana; Wulandari, Retno; Setiyowati, Supami Wahyu (Jurnal Riset Mahasiswa Akuntansi, 2020)
The effect of profitability, capital structure, managerial ownership and independent board of commissioners on the company's value both simultaneously and partially. The technique used in sampling uses a purposive sampling method because in sampling it uses certain criteria. The research was conducted in the period 2016-2018. The analytical method used is multiple linear regression with the SPSS 22 program. The results of the study show that there is simultaneously an influence between profitability, capital structure, managerial ownership and independent board of commissioners on company value and partial profitability which has no influence on firm value, while capital structure, managerial ownership and independent board of commissioner have a significant effect on the value of the company.